The most important of historiographer at the Mameluke period in Egypt (648- 923 H/ 1250- 1517ac) - Sareem, Wafaa; Muhanna, Osama; Rajab, Wael (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research was conducted to study the most important of historiographer in Egypt at the Mameluke period, during (648- 923H/ 1250- 1517ac), by tracing authorship movement in history, and study the order that each of them had followed. The first one we studied was Taki Al Din Al Maqrizi (766- 845H/ 1365- 1441ac), who was during the second Mameluke country, and study his way in historical authorship, especially in his manuscript "the Maqrizian plans" which includes several historical, geographic, economical and social sides. In other hand, we studied the way of Ibn Houjr Al Askalani (773-852H/1372-1448ac) by studying his authorships especially his manuscript about history of Mameluke country in Egypt. In the third hand, we studied Shams Al Din Al Sakhawi (831-902H/1428-1497ac) who was during the last period of Mameluke age. As we studied the relationship between historiographer and regnant authority on chronicle movement in these period.